Segurança jurídica no processo administrativo tributário: uma análise das decisões administrativas no âmbito do CARF - Oliveira, Larissa Fernandes de (Universidade Federal Rural do Semi-Árido, 2018)
Based on the application and effectiveness of the principle of legal certainty, this research proposes to make considerations about the federal fiscal administrative process and the possibility of judicial review of decisions rendered by the Administrative Council of Tax Appeals (CARF) when these are favorable to the taxpayer. To this end, general considerations are made about the fiscal administrative process, analyzing the CARF scenario before and after the Zelotes Operation. Next, an analysis is made of the application of legal certainty in the administrative tax process as a guarantee of the taxpayer. At the last moment, it is sought to analyze the possibility of judicial review of administrative decisions, whether favorable to the taxpayer or the Treasury, proposing authorization requirements for the filing of an annulment action by the Treasury in case of favorable decision to the taxpayer. As for the methodology, bibliographical, documentary and legislative research was used, mainly master's dissertations and doctoral theses. In conclusion, the possibility of questioning the decisions of CARF in a wide and unrestricted manner provokes instability in the Brazilian legal system.
Artigo Acadêmico
Keywords: CARF; Revisão judicial; Segurança jurídica; CARF; Judicial review; Legal certainty; CIENCIAS SOCIAIS APLICADAS::DIREITO